Persistence of Antibody Response Against SARS-CoV-2 After Vaccination - Bekti, Heri Setiyo; Habibah, Nur; Dharmawati, I Gusti Agung Ayu; Merdekawati, Fusvita; Noviar, Ganjar (JURNAL INFO KESEHATAN, 2023)
SARS-CoV-2 is the causative agent of the disease known as COVID-19. COVID-19 is spreading very fast around the world. One of the immune responses that play a role in against SARS-CoV-2 infection is the production of antibodies, which is 3 weeks after infection. Where within 3 weeks after infection, antibodies will be produced against RBD and the S1 and S2 domains in glycoprotein S and nucleocapsid protein N. The ability of an antibody to inhibit viral infection is determined by its level or titer. This study aims to determine the description of antibody levels against SARS-CoV-2 after vaccination. This type of research is descriptive research. Measurement of antibody levels for SRBD SARS-CoV-2 was carried out using the CLIA method using the MAGLUMI tool. Of the 30 respondents, 23 people had received the third vaccine. The results of this study showed that the average level of SRBD antibodies against SARS-CoV-2 in respondents with 2 doses of vaccine (1.063,786 BAU/mL) was higher than in respondents with 3 doses of vaccine (535.651 BAU/mL). Vaccine intervals of more than 6 months (908.338 BAU/mL) have higher antibody levels than respondents with vaccine intervals of 1-6 months (228.006 BAU/mL). The conclusion of this study is the highest antibody titers are produced >6 months after vaccination, antibody titers are still detectable after 12 months of vaccination, and for further research, it can be measured antibody levels against SARS-CoV-2 from people who have got vaccination for a duration of 2 years or more.